Validation of medium range weather forecasts in sub-temperate and sub-humid climate of western Himalayas - RANA, RANBIR SINGH; SOOD, RUCHI; ADITYA, ADITYA; SHEKHAR, J (The Indian Journal of Agricultural Sciences, 2026)
The medium range weather forecasts were observed and compared for their reliability and profitability for the duration of 1994 to 2010 on seasonal and day wise scale. The forecast verification comprised of the anticipated weather information on six weather parameters, viz. rainfall, cloud cover, maximum temperature, minimum temperature, wind speed and wind direction. The forecast of rainfall, maximum and minimum temperature were realized as high as 93.9, 85.2 and 84.1 percent respectively during the post monsoon (October to December) season compared to 53.2, 71.6 and 74.9 percent in the South West (June to September) monsoon period. The Ratio Score for all the seasons ranged from 57.6 to 83.6 and H K scores ranged from 0.14 to 0.48. For rainfall, highest RMSE of 27.1 was recorded in South West monsoon season indicating lower accuracy. The qualitative forecast revealed higher reliability compared to quantitative forecast. The mean annual usability of rainfall, cloud cover, maximum and minimum temperature were 74.8, 64.7, 62.1 and 63.3 percent respectively. RMSE for minimum temperature was found higher than maximum temperature indicating lower accuracy. For all the seasons, forecast of wind speed showed a high range of accuracy, particularly 100 percent accuracy in post monsoon season. Wind direction was found highly inconsistent in all the seasons with low accuracy. Amongst the medium range weather forecasts for different days, 3 days forecast for the duration of 1994-2000 showed higher accuracy in case of cloud cover, maximum temperature, minimum temperature and wind speed in all the seasons. The increase in accuracy was observed for rainfall and wind direction in case of 4 days forecast. The reliability for 5 days forecast was observed to be lowered in comparison to 3 and 4 days forecast. The medium range forecasts tested for major crops showed profit due to weather forecasts based AAS on farmers’ field (2.1 to 5.4%) and university farm (8.9 to 14.7%). The cloud cover forecasts saved 44 to 75 kg fish feed in 100 sq meter area during SW monsoon at Palampur. The temperature forecasts were useful in saving 10 to 20 percent feed in poultry. The farmers’ perceptions revealed a fairly good use of forecast for various agricultural activities. Proper rainfall forecasts for drainage of maize, vegetables and pulses saved Rupees 400 per irrigation.